A preliminary analysis of interleukin-1 ligands as potential predictive biomarkers of response to cetuximab - Madelyn Espinosa-Cotton; Elana J. Fertig; Laura P. Stabile; Autumn Gaither-Davis; Julie E. Bauman; Sandra Schmitz; Katherine N. Gibson-Corley; Yinwen Cheng; Isaac J. Jensen; Vladimir P. Badovinac; Douglas Laux; Andrean L. Simons (BMC, 2019)
Abstract Background The epidermal growth factor receptor (EGFR) monoclonal IgG1 antibody cetuximab is approved for first-line treatment of recurrent and metastatic (R/M) HNSCC as a part of the standard of care EXTREME regimen (platinum/5-fluorouracil/cetuximab). This regimen has relatively high response and disease control rates but is generally not curative and many patients will experience recurrent disease and/or metastasis. Therefore, there is a great need to identify predictive biomarkers for recurrence and disease progression in cetuximab-treated HNSCC patients to facilitate patient management and allow for treatment modification. The goal of this work is to assess the potential of activating interleukin-1 (IL-1) ligands (IL-1 alpha [IL-1α], IL-1 beta [IL-1β]) as predictive biomarkers of survival outcomes in HNSCC patients treated with cetuximab-based chemotherapy. Methods Baseline gene, serum and tumor expression of interleukin-1 (IL-1) ligands were analyzed from The Cancer Genome Atlas (TCGA) database or clinical trials of cetuximab-based therapies and interrogated for associations with clinical outcome data. Results High tumor gene expression of IL-1β was associated with a more favorable overall survival in cetuximab-treated HNSCC patients but not in non-cetuximab-treated patients. In HNSCC patients treated with cetuximab-based chemotherapy, higher gene and circulating levels of IL-1α and IL-1β were correlated with a more favorable progression free survival compared to patients with low or undetectable levels of IL-1 ligands. Conclusions These findings suggest that IL-1 ligands may function as predictive biomarkers for tumor response to cetuximab-based chemotherapy in HNSCC patients and warrants further investigation and validation in larger clinical studies.